Purchasing Behavior and Its Determinants Toward Chicken Eggs in Different Consumer Segments: Evidence From Indonesian Millennial and Z Generations - Kartika, Emeralda Tria; Suprehatin; Asnawi, Yudha Heryawan (Jurnal Manajemen dan Agribisnis, 2024)
As the demand for chicken eggs continues to increase, currently Indonesian consumers also have many choices in the decision to purchase good quality eggs in the context of type, quality and place of purchase of eggs. The diverse quality of egg products in the market shows that the Indonesian egg market is increasingly segmented. This research aims to analyze the purchasing behavior of chicken eggs and the factors influencing purchasing decisions in the millennial and Z generations as Indonesia's largest consumer segments. This research used primary data from both online and offline surveys of 365 respondents in Greater Jakarta. Data were analyzed using descriptive statistics and partial least squares-structural equation modeling. The results showed that the millennial generation tends to purchase eggs more in a month and consider nutritional value, while the Z generation tends to be price oriented. The results also showed that price, purchase location and consumer knowledge significantly positively affected egg purchase decision for both the millennial and Z consumer segments. In addition, millennial consumers also consider product qualities and lifestyle in their chicken egg purchase decision. A better understanding of consumer behaviour for chicken eggs among different segments is vital for marketers to efficiently meet the expected and dynamic consumer demand. Keywords: chicken eggs, consumer segment, millennial generation, purchasing decisions, Z generation